Immune Checkpoint Inhibitor-Induced Limbic Encephalitis during Treatment with Atezolizumab in a Patient with Small-Cell Lung Cancer: A Case Report and Review of the Literature - Koki Nakashima; Yoshiki Demura; Kosuke Kurokawa; Toshihiro Takeda; Norihiro Jikuya; Masahiro Oi; Toshihiko Tada; Masaya Akai; Tamotsu Ishizuka (Case Reports in Immunology)
Paraneoplastic neurological syndrome (PNS) is associated with malignancies, including small-cell lung cancer. Recently, PNS cases among patients with small-cell lung cancer (SCLC) induced by immune checkpoint inhibitors have increased. We herein report a 66-year-old man with SCLC who developed disorientation, dysphagia, and gait disturbance after three courses of treatment with atezolizumab. Brain magnetic resonance imaging revealed a high-intensity area in the bilateral temporal lobes. Blood test results were positive for anti-Hu and anti-Zic4 antibodies, which led to the diagnosis of limbic encephalitis as PNS. Some symptoms improved with intravenous administration of steroids and immunoglobulins.